Evaluation of Information Technology Governance Using Cobit 2019 on Domain DSS (Deliver, Service, Support) at PT XYZ - Atik Zilziana Muflihati Noor; Aris P Widodo; Kusworo Adi (Budapest International Research and Critics University, 2022)
PT. XYZ is an application development company. In business, PT XYZ implements information technology to support its business goals. This governance has the aim of ensuring product results from PT XYZ. This research refers to COBIT® 2019 by using qualitative methods and focusing on the DSS04 Manage Continuity and DSS06 Managed Business Process Controls by carrying out an initial analysis of the company situation and interviews with company employees. Based on the results carried out on the company's products, the maturity level in the domain is between the values of two to four. Cobit results explain that the company's website products are not optimal in their performance.